Sebaceous neoplasms - Flux, Katharina (Surgical pathology clinics, 2017)
Sebaceous skin tumors are classified into sebaceous adenoma, sebaceoma, and sebaceous carcinoma. An additional group of cystic sebaceous tumors indicate the Muir-Torre syndrome (MTS). Cystic sebaceous tumors are considered as morphologic variants of the 3 main categories. Multilineage adnexal tumors with partly sebaceous differentiation may pose a challenge to categorize. Sebaceous hyperplasia and nevus sebaceus are not considered as true sebaceous tumor entities. Recently, attention has been drawn to morphologic clues of sebaceous differentiation. Immunohistochemistry using the mismatch repair proteins and/or genetic microsatellite instability testing should be performed on sebaceous neoplasms to diagnose MTS as early as possible
Gesehen am 09.04.2018